Transferência de rotinas em metaorganizações: estudo de caso em uma instituição universitária - Iwata, Isa Akemi Pires (Universidade do Vale do Rio dos Sinos, 2024)
This dissertation investigates the transfer of routines in an educational metaorganization, focusing on a public university. Metaorganizations, characterized by the interconnection of autonomous units that collaborate to achieve common goals, heavily rely on the effectiveness of organizational routines to disseminate guidelines, policies, and best practices among their various units. The research examines the mechanisms, challenges, and facilitators of the routine transfer process, especially considering an environment subject to constant changes in government policies. The research adopts a comprehensive methodological approach, including a literature review, primary data collection through interviews, and qualitative analysis of the data obtained. Data triangulation was conducted to ensure the validity and reliability of the results by combining different sources of information and analytical methods. The results indicate that the transfer of routines in an educational metaorganization is a complex process influenced by the interaction between organizational strategy and absorptive capacity. Absorptive capacity, which involves the ability to recognize, assimilate, and apply new knowledge, proved crucial for the effective adaptation and implementation of routines. The university’s autonomous units demonstrated significant variations in their capacity to absorb and apply routines, reflecting differences in their organizational structures, cultures, and available resources. Additionally, the research revealed that artifacts, such as documents and information systems, play a fundamental role in sustaining routines, facilitating communication and coordination among the units. In conclusion, this dissertation contributes to the theoretical and practical understanding of routine transfer in metaorganizations, offering valuable insights for managers and academics interested in improving organizational effectiveness and the ability to adapt to changes. The findings suggest the need for specific strategies to strengthen the absorptive capacity of units and promote an organizational culture that values flexibility and innovation.
Keywords: Metaorganizações; Rotinas organizacionais; Transferência de rotinas; Metaorganização educacional; Capacidade absortiva; Metaorganizations; Organizational routines; Routine transfer; Educational metaorganization; Absorptive capacity; ACCNPQ::Ciências Sociais Aplicadas::Administração